2019
DOI: 10.1101/778191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of genes required for body axis and limb formation by global identification of retinoic acid regulated epigenetic marks

Abstract: Identification of target genes that mediate required functions downstream of transcription factors is hampered by the large number of genes whose expression changes when the factor is removed from a specific tissue and the numerous binding sites for the factor in the genome. Retinoic acid (RA) regulates transcription via RA receptors bound to RA response elements (RAREs) of which there are thousands in vertebrate genomes. Here, we combined ChIP-seq for epigenetic marks and RNA-seq on trunk tissue from wild-typ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…Interestingly, 24 RAR sites were found in extremely conserved non-coding regions and sequences could be aligned from zebrafish to human. This is the case for RAR sites located in some hox clusters (Nolte, De Kumar, and Krumlauf 2019), near meis2 (Berenguer et al 2020), nrip1a, ncoa3 and in the skap1 gene (this study). Such high conservation suggests that the level of expression of these RA target genes must be precisely controlled.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Interestingly, 24 RAR sites were found in extremely conserved non-coding regions and sequences could be aligned from zebrafish to human. This is the case for RAR sites located in some hox clusters (Nolte, De Kumar, and Krumlauf 2019), near meis2 (Berenguer et al 2020), nrip1a, ncoa3 and in the skap1 gene (this study). Such high conservation suggests that the level of expression of these RA target genes must be precisely controlled.…”
Section: Discussionsupporting
confidence: 51%
“…This gene set includes many genes previously shown to be regulated by RA in other germ layers like hox, nr2f, cyp26a, dhrs3 or hnf1b genes (Feng et al 2010b; C. E. Love and Prince 2012; Berenguer et al 2020; Hernandez et al 2004; Nolte, De Kumar, and Krumlauf 2019) indicating that the regulatory network triggered by RA is shared, at least partially, between the three germ layers. Analysis of the zebrafish RAR cistrome at the end of gastrulation confirms hox genes as direct RAR targets (Nolte, De Kumar, and Krumlauf 2019), acting on the anterio-posterior patterning of the endoderm, but the data also pinpoint 4 direct RAR target genes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Given that retinoic acid has been shown to regulate Meis expression in different settings (Berenguer et al, 2020;Mercader et al, 2000;Oulad-Abdelghani et al, 1997;Yashiro et al, 2004), we studied whether the elimination Raldh2-mediated RA synthesis affects axial Meis expression. We studied Meis1 and Meis2 mRNA and protein expression in Sox2 Cre ; Raldh2 flox/flox embryos and found that both genes presented a reduction of transcripts along the trunk region of E8 embryos ( Figure 6U-X).…”
Section: Development • Accepted Manuscriptmentioning
confidence: 99%
“…The active form of vitamin-A, retinoic acid (RA), regulates gene expression during embryonic development by binding to nuclear receptors RARα, RARβ or RARγ (Rhinn and Dolle, 2012). Meis genes have been identified in screens for RA targets (Berenguer et al, 2020;Oulad-Abdelghani et al, 1997) and respond to RA fluctuations in vivo (Mercader et al, 2000;Yashiro et al, 2004). RA excess produces axial skeleton alterations and modifies the Hox AP expression domains (Kessel and Gruss, 1991) and mutations in RA-receptor genes result in homeotic transformations, however, the mechanism by which this takes place is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Although several regulatory genes have been identi ed as important downstream targets of RA, such as Hox or Hnf1b genes 8, [15][16][17][18] , the regulatory network triggered by RA in endoderm during gastrulation is still unclear. Many transcriptomic studies have identi ed RA-regulated genes in murine, xenopus or zebra sh embryos [19][20][21][22][23][24][25] ; however these reports were often done on whole embryos and not done speci cally on endodermal tissues. Still two studies performed on xenopus endoderm have nevertheless reported the involvement of Ndrg1, Fzd4 and Hnf1b genes as crucial mediators of RA signalling for pancreas development 18,26 ; however, it is not yet known if the role of these regulatory genes is conserved among vertebrates.…”
Section: Introductionmentioning
confidence: 99%